Comparative analysis of scarf-type adhesively bonded and hand lay-up repairs of impacted GFRP composites. (5th September 2019) - Koricho, Ermias G.; Khomenko, Anton; Karpenko, Oleksii; Haq, Mahmoodul; Cloud, Gary L.
In this paper two types of repair methods were considered: adhesively bonded and hand lay-up scarf-type patches. The performance of both repair techniques applied to impacted/damaged glass fibre reinforced plastic (GFRP) laminates was assessed under tensile and three-point bending tests. In the hand lay-up patches, two types of resins, namely unmodified and nano-modified resins were used to evaluate their effects on the flexural strength and failure modes of the repaired composite specimens. The damage was assessed using visual observation, active IR thermography, ultrasonic testing, and optical transmittance scanning techniques at different stages. Results indicate that, depending on the type of repair and nano-filler used, the flexural properties of the repaired composite specimen exhibited significant improvements. The choice of repair method would vary depending on the desired application along with accessibility to the damaged area. Overall, repair of composites allows considerable economic benefits over the replacement of an entire structural component.